Implementation of the Community Science Technology Model in Civics Learning to Grow Student Social Intelligence - Arnie Fajar; Yadi Supriadi (Universitas Dharma Wacana, 2022)
Advances in science and technology, require all humans in the world to adapt to the situation. Likewise in the field of education in schools. Almost all students in Indonesia use mobile phones as their social media, including students at SMP Negeri 1 Jatinangor Sumedang. Based on observations of students in Civics lessons, it appears that the attitudes of students lack social intelligence, such as lacking problem solving skills, communicating, expressing opinions, and listening to other people's opinions. This study aims to determine how the application of the Community Science Technology Model in growing the social intelligence of students in class VII-1 SMP Negeri 1 Jatinangor Sumedang. The research approach used is qualitative with Classroom Action Research methods. The results showed that there was a growth in the social intelligence of students from cycles I, II, and III. The problem solving skills of students grew from 14 people (cycle I), to 22 people (cycle II), and 24 people (cycle III). The ability to communicate grew from 11 people (cycle I) to 18 people (cycle II), and became 20 people in cycle III. Likewise, students' ability to listen to others grew from 14 people (cycle I) to 19 people (cycle II), and became 20 people in cycle III.